MINDS: a translator to embed mathematical expressions inside SPARQL queries - Graux, Damien; Sejdiu, Gezim; Stadler, Claus; Napolitano, Giulio; Lehmann, Jens (My University, 2020)
The recent deployments of semantic web tools and the expansion of available linked datasets have given users the opportunity of building increasingly complex applications. These emerging use cases often require queries containing mathematical formulas such as euclidean distances or unit conversions. Currently, the latest SPARQL standard (version 1.1) only embeds basic math operators. Thus, to address this shortcoming, some popular SPARQL evaluators provide built-in tools to cover specific needs; however, such tools are not standard yet. To offer users a more generic solution, we propose and share MINDS, a translator of mathematical expressions into SPARQL-compliant bindings which can be understood by any evaluator. MINDS thereby facilitates the query design whenever mathematical computations are needed in a SPARQL query.
PUBLISHED
Keywords: Mathematical logic, set theory, combinatorics, semantics; SEMANTIC WEB; Communication